Pengaruh Bauran Pemasaran (7P) terhadap Keputusan Memilih Pondok Pesantren dengan Trust sebagai Variabel Mediasi pada Pondok Pesantren Sumber Barokah Karawang - Taufik Hidayat (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
The marketing mix has an important role in influencing public (consumer) trust, because each element of the 7Ps contributes to consumer perception of the credibility, reliability, and value offered by an educational product or service. This study aims to analyze the influence of the marketing mix (7P) on the trust of the community/prospective students and the decision to choose the Sumber Barokah Karawang Islamic Boarding School. The research sample amounted to 145 respondents who were determined using purposive sampling techniques. Data collection was carried out through the distribution of questionnaires with a Likert scale of 1–5. The data analysis techniques used include classical assumption tests, multiple linear regression, partial tests (t tests), and simultaneous tests (F tests) with the help of the SPSS version 23 program. The results of the study show that the variables of product, price, promotion, people, process, and physical evidence have a significant effect on public trust/prospective students. Meanwhile, the place variable had no significant effect on trust. Furthermore, the trust variable has been proven to have a significant influence on the decision to choose the Sumber Barokah Islamic Boarding School. These findings show that effective marketing mix management can increase trust and encourage decisions to choose Islamic boarding schools.